Personality traits and the degree of work addiction among Polish women: the mediating role of depressiveness - Kamila Rachubińska; Anna Maria Cybulska; Ewa Kupcewicz; Mariusz Panczyk; Szymon Grochans; Ireneusz Walaszek; Elżbieta Grochans (Frontiers in Public Health, 2023)
ObjectivesWorkaholism is an addiction, however the obsessive-compulsive components alone may prove insufficient in determining its nature. The aim of the following study was to determine the mediating role of depressiveness in the relationships between workaholism and personality traits according to the five-factor model among Polish women.MethodsThe research study was carried out among 556 women residing in the West Pomerania Voivodeship in Poland. The research was based on a survey performed using a questionnaire technique. The following research instruments adapted to Polish conditions were employed to assess the incidence of work addiction among female adults: The NEO Five-Factor Inventory (NEO-FFI), The Work Addiction Risk Test (WART) Questionnaire, and The Beck Depression Inventory–BDI I-II.ResultsA positive correlation between the intensity of neuroticism and the work addiction risk was revealed (β = 0.204, p < 0.001). A partial mediation (35%) with the severity of depression symptoms as a mediating factor was observed (β = 0.110, p < 0.001). Respondents characterized by high neuroticism showed a greater severity of the symptoms of depression (β = 0.482, p < 0.001), which is a factor increasing the work addiction risk (β = 0.228, p < 0.001). No effect of extraversion intensity on the work addiction risk was found (β = 0.068, p = 0.081). Respondents characterized by a high level of extraversion displayed lower severity of the symptoms of depression (β = −0.274, p < 0.001). A negative correlation between the intensity of agreeableness and the work addiction risk was revealed (β = −0.147, p < 0.001). A partial mediation (27.8%) was observed. A positive correlation between the intensity of conscientiousness and the work addiction risk was revealed (β = 0.082, p = 0.047). Respondents characterized by a high level of conscientiousness showed a lower severity of depression symptoms (β = −0.211, p < 0.001).ConclusionDepressiveness plays the role of a mediator between neuroticism, extraversion, agreeableness as well as conscientiousness, and work addiction. Depressiveness is a factor which increases the risk of work addiction.